2011
DOI: 10.1007/s00277-011-1286-0
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, cytogenetics, and survival in myelodysplasia with del(20q) or ider(20q): a multicenter study

Abstract: Isochromosome of the long arm of chromosome 20 with interstitial loss of material [ider(20q)] is a rare cytogenetic abnormality reported in myelodysplastic syndrome (MDS), with neither specific morphological pattern nor clear prognostic significance. The aim of this retrospective multicentric study is to compare the peripheral blood and bone marrow morphology of MDS patients with ider(20q) (n = 13) and del(20q) (n = 21) and controls (n = 47) in order to investigate whether the ider(20q) harbors specific morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
1
11
0
1
Order By: Relevance
“…Mice haplo-insufficient for Mybl2 develop a variety of myeloid disorders including a myelodysplastic syndrome (MDS) and myeloid leukaemia 102, 103 . MYBL2 is present in the 20q locus that is frequently deleted in human MDS 104, 105 . Although the precise mechanism by which low levels of BMYB expression translates into abnormal myeloid cell proliferation is unclear, it is likely to involve BMYB's role in regulating cell cycle dependent gene expression.…”
Section: Dream Disruption In Cancermentioning
confidence: 99%
“…Mice haplo-insufficient for Mybl2 develop a variety of myeloid disorders including a myelodysplastic syndrome (MDS) and myeloid leukaemia 102, 103 . MYBL2 is present in the 20q locus that is frequently deleted in human MDS 104, 105 . Although the precise mechanism by which low levels of BMYB expression translates into abnormal myeloid cell proliferation is unclear, it is likely to involve BMYB's role in regulating cell cycle dependent gene expression.…”
Section: Dream Disruption In Cancermentioning
confidence: 99%
“…Prognosis of MDS patients with an ider(20q) remains controversial. In some reports, a low complete remission rate and a high mortality rate were described for these patients (Li et al , ), whereas others described rather indolent courses (Ligon et al , ) and found no significant differences in the outcomes of patients with an ider(20q) as compared to patients with del(20q) (Mullier et al , ).…”
mentioning
confidence: 98%
“…GPI anchor protein-deficient cells have been detected in some cases of myelodysplastic syndrome, especially when associated with a hypocellular marrow [2] as in our patient, where bone marrow aspiration and bone marrow biopsy were diagnostic of MDS using standard criteria and where cytogenetics showed an interstitial deletion of the long arm of chromosome 20. This deletion is usually classified in the good-prognosis MDS category with a median overall survival > 5 years [10]. CBCs were stable during 2 years without any transfusion needs.…”
Section: Discussionmentioning
confidence: 99%